Solitary symbolic play, object substitution and peer role play skills at age 3 predict different aspects of age 7 structural language abilities in a matched sample of autistic and non-autistic children. (January 2022) - Zhao, Yiran Vicky; Gibson, Jenny Louise
Backgrounds and aims: Early symbolic play abilities are closely related to long-term language development for both autistic and non-autistic children, but few studies have explored these relations for different dimensions of pretence and of language. The current study explores carer-reported measures of solitary symbolic play, object substitution and peer role play abilities at age 3, and their respective relations with parent-reported semantics, syntax and narrative abilities at age 7 for both autistic and non-autistic children. Methods: We conducted secondary data analyses exploring links between different aspects of pretence and of language on the Longitudinal Study of Australian Children population cohort. We identified 92 autistic children and used propensity score matching to match them with 92 non-autistic children based on demographic and developmental information such as non-verbal IQ and socioeconomic status. We explored concurrent and longitudinal relations using correlation and regression models.Results: Both correlational and hierarchical regression analyses confirmed the significant effects of age 3 symbolic play abilities in facilitating age 7 semantics, syntax and narrative abilities for autistic children. We found that object substitution held most prominent influence, followed by peer role play and solitary symbolic play. In contrast, for non-autistic children, none of the age 3 symbolic play abilities were significant predictors, whereas socioeconomic status at birth and age 3 language abilities held significant influences on their age 7 semantics, syntax and narrative abilities.Conclusion: We discuss the implications of our findings for play interventions targeting language outcomes.